Anopheline (Dipters: Culicidae) breeding in a traditional tank-based village ecosystem in north central Sri Lanka - Amerasinghe, Felix P.; Konradsen, Flemming; Fonseka, K.T.; Amerasinghe, Priyanie H. (1997)
A 13-mo survey of immature anopheline mosquitoes breeding in surface water habitats was done at Mahameegaswewa village within the Huruluwewa watershed in north central Sri Lanka as part of a multidisciplinary study on malaria epidemiology. The watershed is representative of the ancient small tank-based irrigation network that still forms an important component of the rice production system in the low elevation dry zone. In total, 3,818 immatures representing 12 species were obtained from 2,940 samples taken from 5 larval habitats within the village ecosystem. Anopheles varuna Iyengar and An. culicifacies Giles were the most abundant species collected. Peak abundance in both species occurred in August-October. Anopheles barbirostris Van der Wulp and An. peditaeniatus Leicester also were abundant, but neither these nor the other anophelines attained comparable abundance to An. varuna and An. culicifacies. A clear progression in breeding habitat use from stream bed to tank bed and drainage area pools was seen in An. culicifacies during the premonsoon period. Environmental management measures to reduce or modify these habitats could potentially decrease malaria transmission.